Clarifying Ethical Intuitionism. (15th April 2013) - Cowan, Robert
Abstract: In recent years there has been a resurgence of interest in Ethical Intuitionism, whose core claim is that normal ethical agents can and do have non‐inferentially justified first‐order ethical beliefs . Although this is the standard formulation, there are two senses in which it is importantly incomplete. Firstly, ethical intuitionism claims that there are non‐inferentially justified ethical beliefs, but there is a worrying lack of consensus in the ethical literature as to what non‐inferentially justified belief is. Secondly, it has been overlooked that there are plausibly different types of non‐inferential justification, and that accounting for the existence of a specific sort of non‐inferential justification is crucial for any adequate ethical intuitionist epistemology. In this context, it is the purpose of this paper to provide an account of non‐inferentially justified belief which is superior to extant accounts, and, to give a refined statement of the core claim of ethical intuitionism which focuses on the type of non‐inferential justification vital for a plausible intuitionist epistemology. Finally, it will be shown that the clarifications made in this paper make it far from obvious that two intuitionist accounts, which have received much recent attention, make good on intuitionism's core claim.